Bau Ist Kunst - Ist Bau Kunst. - steirischer herbst, Graz (Graz : Steirischer Herbst, 1986)
Botta, Mario ; Cook, Peter ; Domenig, Günther ; Hejduk, John ; Graves, Michael ; Hollein, Hans ; Kowalski, Karla ; Von Kostelac, Ante Josip ; Natalini, Adolfo ; Peichl, Gustav ; Stelzhammer, Walter ; Tröthan, Martin
catalogue to the symposium Bau Ist Kunst : Ist Bau Kunst / Building Is Art : Is Building Art, Steirischers Herbst '86, Graz
boek